Validation of Methylene Blue Analysis Method in Wastewater Samples by UV-Vis Spectrophotometry - Hulupi, Mentik; Keryanti, Keryanti; Rahmawati, Karina Aulia; Dewi, Widya Tresna; Abdilah, Fauzi (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Methylene blue (MB) is an extensively utilized cationic dye in the textile industry. MB is, however, a highly noxious substance that can have detrimental effects on both the environment and human health. MB can pollute waterways and cause the mortality of aquatic organisms in the environment. Due to the hazards posed by MB, it is crucial to have an effective method for analyzing its concentration in wastewater. This will ensure that MB-contaminated water is appropriately treated and disposed of, thereby protecting the environment and human health. One of the analyses utilized the Evolution 360 UV-Vis Spectrophotometer to determine methylene blue concentrations. The Evolution 360 UV-Vis Spectrophotometer method was validated by measuring linearity tests, limit detection and quantization, precision, and accuracy. The R-value for linearity measurements is greater than 0.99, indicating that the method is proportionally validated. As required, the precision measurement yields acceptable results, with a %RSD value of less than 2%, and the accuracy measurement yields a recovery of 100% (between 80 and 110%). So that the method for measuring the concentration of methylene blue in water using the UV-Vis Evolution 360 Spectrophotometer satisfies the requirements for linearity, precision, and accuracy.Keywords:Analysis, Methylene Blue, Method Validation, Spectrophotometer